L-PROLIN SEBAGAI AGEN EUTEKTIK UNTUK MENINGKATKAN KELARUTAN ASAM MEFENAMAT DAN GARAM MEFENAMAT - Rachma Hakiki, Arini
Mefenamic acid is an NSAID used in short term pain management. Mefenamic acid has poor solubility, and improving its solubility is deemed essential to increase efficacy. Forming an eutectic mixture with a coformer is a method known to increase the solubility of poorly soluble APIs. In this study, the formation of eutectics of mefenamic acid, sodium mefenamate, and potassium mefenamate with Lproline as a coformer is observed, and the increase in solubility is predicted. Sodium and potassium salts of mefenamic acid are formed. Then, eutectic mixtures are formed between the three active compunds with L-proline using the neat grinding method. The formed salts and eutectic mixtures are characterized using electrothermal analysis, FT-IR, and DTA/TG. Then, a literature study was done to predict the solubility improvement of the formed eutectic mixtures. Electrothermal analysis dan FT-IR analysis confirmed the formation of sodium mefenamate and potassium mefenamate. Screening by electrothermal method showed eutectic points at 4:6 molar ratio for MFA-LPR, 6:4 for NaMFA-LPR, and 4:6 for KMFA-LPR. FT-IR analysis on the formed eutectic mixture showed no new peaks in the spectra of MFA-LPR, NaMFA-LPR, and KMFA-LPR eutectic mixtures. DTA/TG analysis showed that Lproline lowered the melting point of MFA-LPR (1:1) to 174,2°C, NaMFA-LPR (1:1) to 116,2°C and 124°C, and KMFA-LPR (1:1) to 126,3°C. The data shows that the mixture is an eutectic mixture. Literature study showed that eutectic mixtures with L-proline as a coformer showed good potential to increase the solubility of mefenamic acid, sodium mefenamate, and potassium mefenamate. In conclusion, an eutectic mixture formed between mefenamic acid, sodium mefenamate, and potassium mefenamate, and the formation of eutectic mixtures was found to have the potential to increase the solubility of mefenamic acid.